The small x behavior of the gluon strucutre function from total cross-sections - Luna, E. G S [UNESP]; Natale, Adriano Antonio [UNESP]; Zanetti, C. M. [UNESP] (World Scientific Publ Co Pte Ltd, 2008)
Within a QCD-based eikonal model with a dynamical infrared gluon mass scale we discuss how the small x behavior of the gluon distribution function at moderate Q(2) is directly related to the rise of total hadronic cross-sections. In this model the rise of total cross-sections is driven by gluon-gluon semihard scattering processes, where the behavior of the small x gluon distribtuion function exhibits the power law xg(x, Q(2)) = h(Q(2))x(-epsilon). Assuming that the Q(2) scale is proportional to the dynamical gluon mass one, we show that the values of h(Q(2)) obtained in this model are compatible with an earlier result based on a specific nonperturbative Pomeron model. We discuss the implications of this picture for the behavior of input valence-like gluon distributions at low resolution scales.
Keywords: dynamical gluon mass; gluon structure function